In Vitro Study on the Effect of Acidic Beverages on the Shear Bond Strength of Orthodontic Brackets - Md. Abdul J. Bougadi; Amarnath Reddy; Amarnath Biradar; Vaishnavi Telang; V. S Bharathi; Abikshyeet Panda; Miral Mehta; Dipooja Patil (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: The strength of the binding between the orthodontic brackets and the tooth surface is a major factor in the outcome of orthodontic therapy. Patients often drink acidic drinks, which might weaken the binding and cause bracket failure. Materials and Procedures: Based on the kind of immersion solution used, 60 removed human premolar teeth were divided into three groups (n = 20) at random: Groups 1 (control) and 2 were submerged in distilled water, cola, and orange juice, respectively. A light-cured adhesive technique was used to attach the metal orthodontic brackets to the teeth. After undergoing a thermocycling procedure to mimic fluctuations in oral temperature, each sample was submerged in its corresponding solution for 10 minutes, three times a day, for 30 days. A universal testing equipment was used to determine the shear bond strength. Megapascals (MPa) were used to record SBS values. Results: Group 2 (cola) had a substantially reduced mean SBS of 9.8 ± 1.5 MPa, Group 3 (orange juice) had a mean SBS of 10.2 ± 1.3 MPa, and Group 1 (control) had a mean SBS of 14.5 ± 1.2 MPa. In comparison with the control, both acidic beverage groups showed a substantial decrease in SBS (P < 0.05). The cola and orange juice groups did not, however, vary significantly (P > 0.05). Conclusion: Orthodontic brackets’ shear bond strength is considerably decreased by exposure to acidic drinks. To avoid bracket debonding and treatment delays, patients receiving orthodontic treatment should be counselled to limit their intake of acidic beverages.